Can patients with mild post-operative hyponatraemia following elective arthroplasty be discharged safely? A large-scale service evaluation suggests they can. (March 2022) - Macdonald, Jonathan; Cunningham, Emma; Gallagher, Nicola; Hamilton, Paul; Cassidy, Roslyn; Bryce, Leeann; Beverland, David
Background: Post-operative hyponatraemia is common following arthroplasty. Clinical hyponatraemia guidelines lack detail on when treatment is necessary, and there is a paucity of literature to guide best practice. Methods: Data were collected within retrospective service evaluations over two time periods in a single high throughput joint unit. The hospital's electronic database identified 1000 patients who were admitted electively between February 2012 and June 2013 and again between November 2018 and April 2019 for primary total hip, total knee or uni-compartmental knee arthroplasty. Hyponatraemia and non-hyponatraemia groups were compared. Logistic regression analysis was used to identify independent predictors of post-operative hyponatraemia, length of stay (LOS), re-attendance or re-admission to hospital. Results: Between 2012–2013 and 2018–2019, 32.1% and 25.7% of patients, respectively, developed post-operative hyponatraemia (serum sodium (s[Na]) ≤135 mmol/L). Those with post-operative hyponatraemia were significantly older, weighed less, were more comorbid and had lower pre-operative sodium. Multivariate analysis showed that increased age, knee surgery and lower pre-operative s[Na] independently predicted post-operative hyponatraemia. Post-operative hyponatraemia did not independently predict LOS, re-attendance or re-admission to hospital, within 90 days, in either cohort. Conclusion: Post-operative hyponatraemia is common and may be a marker of pre-operative vulnerability. In these cohorts, it was not independently associated with LOS, re-attendance or re-admission to hospital. We suggest that otherwise well patients with mild hyponatraemia can be safely discharged earlier than is often the case and may not require extensive investigation. Further examination and research is required to develop a pre-operative approach to predict which patients will develop significant post-operative hyponatraemia.